Analysis of factors affecting the quality of Bintan District government financial reports - Muhammad Isa Alamsyah; Chablullah Wibisono; Bambang Satriawan (Goodwood Publishing, 2023)
Purpose: This study aims to analyze and provide empirical evidence regarding the influence of Fixed Asset Administration, Human Resource Competency, and Regional Government Accounting Systems on the Quality of Government Financial Reports with the Government's internal control system as a moderator. Research methodology: This study used primary data using a quantitative approach. The primary data collection method was a questionnaire that was measured using a Likert scale. Results: The test results show that Fixed Asset Administration has a significant effect on the Quality of Regional Government Financial Reports with a P-Value of 0.000 < 0.05. Limitations: This study analyzes the limitations of the format used by the Bintan District Government for financial reports and how it impacts their quality. Contributions: This study investigates the factors affecting the quality of financial reports produced by the Bintan district government. By analyzing these factors, this study aims to provide valuable insights that can guide efforts to improve the quality of financial reporting in the district. Practical Implications: The findings of this study can be used by policymakers and practitioners to develop strategies to enhance financial reporting quality in Bintan District. This study can also serve as a guide for other local governments seeking to improve their financial reporting practices and standards. Novelty: This study is unique in its focus on the Bintan district government and its efforts to identify factors that influence financial reporting quality.